Kenya - Community Driven Development : Challenges and Opportunities - World Bank (Washington, DC, 2013)
The overall objective of this analytical work is to assess the possibilities for using a community driven development approach in Kenya, to increase formal linkages, downward accountability of service delivery mechanisms, and social inclusiveness in the poverty reduction effort. The report explores relevant policy, and institutional features which color the community driven development (CDD) experience in the country. In the attempt to summarize existing data, and experience on CDD, the focus remains on the various institutional approaches used by different programs. These include a wide spectrum from government and non-government, including a look at the enabling legal, and administrative environment for community mobilization, and civic engagement. Initially, the report provides a background, and introduction to the study, and in analyzing the CDD, aims to inform the Government's the Poverty Reduction Strategy Paper process, and the Bank's Country Assistance Strategy. It then reviews major policies which had impacted the present socioeconomic circumstances, and attempts at CDD. This policy analysis mainly focuses on institutional issues, covering interactions between provincial administration, central line ministries, and local government, and service delivery. Recommendations suggest the instutionalisation of villages, empowerment and improvement of local authorities functioning, and, the design of a supportive development administration, options viewed not as mutually exclusive, but designed to provoke stakeholder discussions.